Student Achievement: Assessing the Impact of Project-Based Blended Learning on Academic Scores in the English Department - Sarwadi; Mujtahidin; Syaiful Huda (Universitas Islam Lamongan, 2024)
Project-Based Blended Learning is an educational method that integrates conventional classroom instruction with online learning and practical projects. The technique used in this research was quantitative; the research aim was to investigate the impact of Project-Based Blended Learning to improve students’ academic achievement in the English department of Qamarul Huda University. The result of this study was Improved Academic Performance and Increased student engagement and Motivation; the combination of project-based learning and online resources can increase student motivation by providing meaningful and relevant learning experiences. When students see the real-world applications of their learning and have the autonomy to explore topics of interest, they are more likely to excel academically. It was shown in the data analysis that before applying project-based blended learning, students got an average score of 77.00, and after applying project-based blended learning, students increased their score to 87.00.